Respuesta :

Given that y=f(g(x)) this implies that y is formed by composition of the function of the functions f(x) and g(x) given by f ο g (x).
thus:
y=f(g(x))=3/(sqrt 3x)+4
breaking down the above it implies that the functions f(x) and g(x) will be:
f(x)=x+4
g(x)=3/(sqrt 3x)

Question:

Consider function f.

[tex]f\left(x\right)=\sqrt{3x-6}[/tex]

Which graph represents function f?

( graphs in photo below )

W. X.

Y. Z.

1. W

2. X

3. Y

4. Z

Answer:

2. X

Explanation:

( In photo below )

Ver imagen websitetechie
Ver imagen websitetechie
ACCESS MORE

Otras preguntas